If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 6x = 4x + 12 Reorder the terms: 10 + 6x = 12 + 4x Solving 10 + 6x = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 10 + 6x + -4x = 12 + 4x + -4x Combine like terms: 6x + -4x = 2x 10 + 2x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 10 + 2x = 12 + 0 10 + 2x = 12 Add '-10' to each side of the equation. 10 + -10 + 2x = 12 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = 12 + -10 2x = 12 + -10 Combine like terms: 12 + -10 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 6x-3=25+2x | | sqrt-2v+7=v-2 | | 2x+4=3x+(-1) | | -x+9=34-6x | | 14x-8=104 | | -6x-3=-33 | | x^2+12x+20=8 | | 3(5-a)-33=21a-6(3+4a) | | 8x-15 = 1 | | y-3/4=2 | | 2u=5 | | (1-lnx)*2x=0 | | s=-16t^2+15t+40 | | x-3y=-40 | | 3-5x=8x | | br^2-44r+120=-30 | | 3y+8x=128 | | 126/((216/6)/6) | | 3y+8=128 | | (-64)^(4/3)=0 | | 19=-d+13 | | (-64)^4/3=0 | | 4.5(x+4)=54 | | g+-16g+-16g=-7 | | 3/63 | | 4.1x-19=26.1 | | 4p-4p=7 | | -4u-7=1 | | V(x)=(12-2x)(12-2x)(x) | | 3r-r+2=12 | | 6x-22=58+4x | | .03x=1391.82 |